The effects of cultural diversity on employees' job satisfaction in a manufacturing industry - Gan, Tchin Xui. (Universiti Malaysia Sarawak (UNIMAS), 2015)
Job satisfaction is an important element to be determined in workforce as it has been linked directly with job performance and indirectly with organizational productivity or effectiveness.This is essential especially in today's diverse workforce. Thus, the main purpose of this research is to find out whether there is an effect of the employees' diverse cultural background towards their job satisfaction by using Independent Samples T-test and One-Way Analysis of Variance (ANOVA). The diverse cultural background refers to gender, age, race, level of education, income level and marital status. This study was conducted among 145 respondents from one of the manufacturing industries located at Sarawak, Malaysia. Cross-sectional studies and questionnaire were used to collect the required data. The result showed that level of education was the only variable that has a significant effect on the employees' job satisfaction among the other variables being studied in this research.